ANALISIS PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN DI PT PUMP - Pramadhani, Garin; Sri Zetli (LPPM Universitas Putera Batam, 2025)
This study aims to analyze the effect of workload and job stress on employee performance using a quantitative descriptive approach. Workload was measured using the NASA-TLX method, while job stress was measured using the Health and Safety Executive (HSE) indicator. Data were collected from 15 employees working at PT Prathama Usaha Mandiri Perkasa through a questionnaire, then analyzed using multiple linear regression using SPSS. The results showed that workload had a significant negative effect on performance (t = -3.505; p < 0.05), as well as job stress (t = -2.917; p < 0.05). The results of the F test (F = 9.016; p < 0.05) also proved a simultaneous influence. This study states that high workload and unmanaged stress can reduce employee performance. Therefore, companies are advised to manage the division of tasks and provide support in stress management to improve employee performance.